Disorder at the Start: The Contribution of Dysregulated Translation Initiation to Cancer Therapy Resistance - Sunavala-Dossabhoy, Gulshan (Frontiers in Oral Health, 2021)
Translation of cellular RNA¬ to protein is an energy-intensive process through which synthesized proteins dictate cellular processes and function. Translation is regulated in response to extracellular effectors and availability of amino acids intracellularly. Most eukaryotic mRNA rely on the methyl 7-guanosine (m7-G) nucleotide cap to recruit the translation machinery, and the uncoupling of translational control that occurs in tumorigenesis plays a significant role in cancer treatment response. This article provides an overview of the mammalian translation initiation process and the primary mechanisms by which it is regulated. An outline of how deregulation of initiation supports tumorigenesis and how initiation at a downstream open reading frame (ORF) of Tousled-like kinase 1 (TLK1) leads to treatment resistance is discussed.